Pengembangan Alat Fleksibilitas (Sit and Reach Box) Berbasis Digital - Nopi Hariadi; Zaenul Arkanudin; Rina Nopiana; Muhammad Husni Tamim (Departemen Kesehatan Dan Rekreasi Fakultas Ilmu Keolahragaan Universitas Negeri Padang, 2026)
This study focuses on the development of a digital-based tool known as the Sit and Reach box, designed to measure back and hamstring flexibility with improved accuracy, efficiency, and practicality over traditional manual devices. The development of instruments capable of displaying measurement results in real-time, reducing reading bias, and accelerating the data recapitulation process is an urgent need in the Physical Education study program. Utilizing the Research and Development (R&D) methodology, specifically the Borg & Gall model, the research involved 25 students for validity testing and 75 students and athletes for reliability testing. The instrument integrates Arduino R3 technology alongside an HC-SR04 ultrasonic sensor and a digital LCD within a modified sit-and-reach box. Data analysis was performed through the Product-Moment validity test and Cronbach’s Alpha reliability test, yielding results that indicated high validity and reliability for the tool. The final product was deemed feasible, practical, and user-friendly while enhancing measurement efficiency, reducing reading bias, and accelerating data recap processes. Furthermore, the study established flexibility assessment norms to aid in evaluating flexibility levels. This digital flexibility test tool is thus suitable for application in practicum classes, physical condition assessments, and coaching, and holds potential for future developments in digital application integration and broader distribution to educational and sports organizations.